2022
DOI: 10.1111/tid.13827
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection with SARS‐CoV‐2 in solid‐organ transplant recipients: Incidence density and convalescent immunity prior to reinfection

Abstract: Background Long‐term protective immunity to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) remains poorly characterized, particularly in solid organ transplant (SOT) patients. Method We determined the incidence density of SARS‐CoV‐2 reinfection in a cohort of adult SOT recipients initially infected between March 1st, 2020 and March 30th, 2021 and included those with initial infection before or after transplantation. Incidence density was the total cases di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…Of the 3282 papers initially retrieved, we included 91 cohort studies evaluating the onset of reinfection, severe and very severe/lethal COVID‐19 among 15,034,624 previously infected subjects (Figure 1), either among health care workers (27 publications; n = 37,598 2,8,9,15,17,24,36,38,42–59 ) or in the general population (67 publications; n = 14,997,026 3–7,10,12,16–23,25–27,43,49,60–106 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 3282 papers initially retrieved, we included 91 cohort studies evaluating the onset of reinfection, severe and very severe/lethal COVID‐19 among 15,034,624 previously infected subjects (Figure 1), either among health care workers (27 publications; n = 37,598 2,8,9,15,17,24,36,38,42–59 ) or in the general population (67 publications; n = 14,997,026 3–7,10,12,16–23,25–27,43,49,60–106 ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table S1, most of the included studies ( n = 43) were carried out in Europe, 2,4–10,12,15,17,18,21,24,26,36,38,44,46–51,58,66,69,71,72,75,81,85–88,91–93,95,99,102 24 in the USA, 20,22,23,25,42,43,57,59,63,67,77,79,82–84,89,90,97,98,103,105–107 18 in Asia 3,16,19,27,45,52–54,56,60,62,64,65,70,73,74,100,101 and the remaining six in South America or South Africa 61,68,80,94,96,104 . The mean age of the participants ranged from 15 to 87 years, and the average follow‐up ranged from 29 to 371 days.…”
Section: Resultsmentioning
confidence: 99%
“…found that SOT patients infected with SARS‐CoV‐2 are at high risk for re‐infection. 1 We agree that in the case of SOT, the immunological response to COVID‐19 may differ from that of healthy people. The current research can show that re‐infection is a possibility.…”
mentioning
confidence: 57%
“…We would like to share ideas on the publication “Re‐infection with SARS‐CoV‐2 in solid‐organ transplant (SOT) recipients: Incidence density and convalescent immunity prior to re‐infection. 1 ” Even after establishing cellular and humoral immune responses, Morris et al. found that SOT patients infected with SARS‐CoV‐2 are at high risk for re‐infection.…”
mentioning
confidence: 99%
“…We would like to reply to the letter from Sookaromdee and Wiwanitkit 1 concerning our publication “Re‐infection with SARS‐CoV‐2 in solid‐organ transplant (SOT) recipients: Incidence density and convalescent immunity prior to re‐infection.” 2 …”
mentioning
confidence: 99%